PENGAMANAN POLYALPHABETIC DENGAN AFFINE CIPHER BERDASARKAN BARISAN FIBONACCI - Astuti, Lestari Fidi; Santoso, Kiswara Agung; Kamsyakawuni, Ahmad (Majalah Ilmiah Matematika dan Statistika, 2019)
Affine cipher is a classic cryptographic algorithm substitution technique. Substitution technique is the encryption process for every character in the plaintext will be subtituted by another character. Affine cipher uses two types of keys. Each character of plaintext to be encrypted substituted by the same key. This research discusses about modify one of the key affine cipher, to produce a different key that will be substituted with each plaintext character. Key modifications are made by the Fibonacci sequence rules. This study also compares affine cipher and key modification affine cipher by finding corelation coeffiecient values. The results obtained from the comparison of the two algorithms, encryption that uses affine cipher key modification is better than affine cipher. Keywords: Cryptography, Affine Cipher, Fibonacci, Correlation Value